Status i prestiż oświeceniowej polszczyzny w świetle uwag Adama Kazimierza Czartoryskiego - Hawrysz, Magdalena (Forum Lingwistyczne, 2018)
Status and Prestige of the Polish Enlightenment Language in the Light of Adam Kazimierz Czartoryski’s Comments The aim of the study is to reconstruct the views on the status and prestige of the Polish language in the end of the 18th century in the light of the book by Adam Kazimierz Czartoryski Myśli o pismach polskich. The work is cognitively attractive, as it gives a testimony to the status and prestige of the Polish language in the breakthrough period for the Polish state, i.e. just after the Third Partition, and even before the intensification of the tendencies to deprive Poles their national identity. In his book Myśli o pismach polskich, the author expresses an unshakable view of the high status of Polish and the shattered prestige. Institutions such as stable state power, capital, intellectual elites, scientific and critical publishing houses, periodicals, schools, theaters, the family can be distinguished among the factors shaping both spheres. Key words: status of language, prestige of language, the Enlightenment, Polish under the partitions, Adam Kazimierz Czartoryski